Rapid detection of NT-proBNP from whole blood using FET based biosensors for homecare - Sarangadharan, Indu; Huang, Shu-Wen; Kuo, Wen-Che; Chen, Po-Hsuan; Wang, Yu-Lin (Sensors and actuators. B, Chemical, 2019)
•FET biosensor for protein detection in whole blood.•High field modulated extended gate FET biosensor design.•Detection of NT-proBNP in 1X PBS with 4% BSA and whole blood.•Surface functionalization and sensitivity.•Home-care diagnostics. Detection of protein biomarkers in blood has diagnostic and prognostic potential in diseases such as heart failure (HF). But currently diagnostics for short term HF biomarkers such as NT-proBNP are only available in the clinical settings which require sophisticated laboratory-based instruments that are costly, complex and time-consuming. We have developed a portable and biosensor system to carry out a rapid whole blood immunoassay to detect NT-proBNP using a field effect transistor (FET) based biosensor. The biosensor has short response time (5 min) and does not require additional sample pre-processing. The biosensor utilizes an electrical double layer (EDL) gated FET, with enhanced sensitivity in high ionic strength solution. The FET biosensor adopts an extended gate format with high electric modulation which enables very high sensitivity, selectivity and wide dynamic range of detection in whole blood. The sensitivity is also correlated with the surface functionalization of the FET biosensor. A portable, hand-held biosensor measurement unit is used to measure and record the electrical signals from the sensor chips which can be used in a ‘dispose after use’ format. In this study, we have demonstrated the detection of NT-proBNP in 1X PBS and whole blood. This sensor is intended for personal home-care diagnostics.